Learning Motivation as a Predictor of Academic Success: A Literature Review in Educational Psychology - Hendrilia, Yudi; Salamah, Salamah; Judijanto, Loso; Nuryenda, Endang Yuda; Fauzi, Muhammad Sukron (The Future of Education Journal, 2025)
This study aims to examine the role of learning motivation as a predictor of academic success through a literature review approach in the field of educational psychology. Using a descriptive qualitative method, data were obtained from various national and international scientific literature sources. The findings indicate that learning motivation, particularly intrinsic motivation, has a significant relationship with students’ academic achievement. Students with high learning motivation tend to be more active, diligent, and capable of applying effective learning strategies, which positively impacts their academic performance. These findings are supported by various motivation theories, such as Self-Determination Theory and Expectancy-Value Theory, and are in line with national education policies that emphasize the importance of holistic student development. In conclusion, learning motivation plays a crucial role in determining academic success, and strengthening this aspect should be a focus in the planning and implementation of the learning process at all levels of education.